A comprehensive mechanistic study on the proton FLASH sparing effect in zebrafish embryos: From DNA damage to developmental abnormalities - Bogaerts, Eva; Saade, Gaëlle; Macaeva, Ellina; Chiavassa, Sophie; Evin, Manon; Haddad, Ferid; Isebaert, Sofie; Koumeir, Charbel; Mouchard, Quentin; Potiron, Vincent; Servagent, Noël; Supiot, Stéphane; et al. (Radiotherapy and oncology, 2025)
•Mechanistic study of zebrafish embryo response after FLASH vs. CONV irradiation.•Proton FLASH reduces radiation-induced DNA damage.•Proton FLASH affects expression of genes involved in cell cycle and p53 regulation.•Proton FLASH reduces apoptosis induction in the embryonic tail.•Natural variation in embryo batch radiosensitivity may impact FLASH sparing effect. Ultra-high dose rate (UHDR) irradiation induces less normal tissues toxicities compared to conventional dose rate (CONV) irradiation. We aimed to assess whether UHDR and CONV proton irradiation result in different levels of DNA damage in zebrafish embryos. Moreover, we studied the downstream transcriptional activation and functional changes following both modalities. Zebrafish embryos received 30 Gy UHDR (>5100 Gy/s) or CONV (0.18 Gy/s) proton irradiation at 28 h post-fertilization on a 68 MeV cyclotron. DNA damage was assessed at 4 h post-irradiation. Gene expression changes were assessed at 6 and 24 h post-irradiation. Apoptosis, proliferation and neutrophil migration were investigated at 6 h and 20 h post-irradiation. Survival and morphological abnormalities were assessed at 4 days post-irradiation. No significant differences in morphological abnormalities were found between treatment groups. Conversely, significantly higher levels of DNA damage were observed in CONV- versus UHDR-irradiated embryos. CONV irradiation resulted in higher expression levels of genes involved in cell cycle arrest (cdkn1a) and p53 regulation (mdm2). Lastly, CONV irradiation resulted in higher levels of apoptosis in the embryonic tail compared to UHDR irradiation. Comparable cell proliferation and neutrophil migration to the sites of injury was found between treatments. UHDR proton irradiation induces less DNA damage and less downstream transcriptional activation of DNA damage response pathways in zebrafish embryos compared to CONV irradiation, resulting in reduced embryonic cell death. However, the magnitude of observed differences might not always be high enough to translate into significant differences in developmental abnormalities.